Hubungan Religiusitas dengan Psychological Well-Being pada Santri di Pondok Pesantren Al-Mutmainnah Desa Leseng Kab. Sumbawa - Junaidin Junaidin (Journal on Education, 2023)
The purpose of this study was to determine the relationship between religiosity and psychological well being in students at the Al Muthmainnah Islamic boarding school in Leseng Village. This study uses a descriptive quantitative approach and uses a sampling technique using a cluster sampling technique to determine the number of samples using the Slovin Formula. The sample in this study consisted of 74 students at the Al Muthmainnad Islamic boarding school in Leseng village. The research data was obtained using research instruments in the from of two scales, namely the scale of religiosity and the scale of psychological well being. The result showed that there was a positive and significant relationship between religiosity and psychological well being with a correlation coefficient value of 0,0598 with a calculated p value = 0,005 or p < 0,05 which means the higher the religiosity, the higher the psychological well being and vice versa. The lower the religiosity, the lower the psychological well being of the students at the Al Mutmainnah Islamic boarding school in Leseng Village.